Care guide for patients with class II malocclusion with actively growing permanent dentition - Félix Adjei Tannor; Olga Lidia Véliz Concepción; Waldo Pérez Garcia; Armando San Miguel Pentòn (Medisur, 2024)
Foundation: Class II malocclusion has the highest prevalence among dentoskeletal disorders. Objective: to propose a care guide for patients with class II malocclusion with actively growing permanent dentition. Methods: a mixed approach technological innovation research was carried out in the Clinical Sciences Department from the Stomatology Faculty of the Villa Clara Medical Sciences University, from 2020 to 2023. The studied universe was all the Orthodontic specialists in the Villa Clara province, Sancti Spíritus and Cienfuegos, from which an intentional non-probabilistic sampling was carried out by criteria and the sample was made up of 20 specialists and seven experts (higher category specialists) with criteria of inclusion. Results: The reviewed documentation provided valuable information to determine the current state of care for malocclusion under study. Specialists issued different criteria on the diagnosis and treatment of class II malocclusion. The experts established the invariable elements for their classification. Finally, a care guide was designed for patients with class II malocclusion with actively growing permanent dentition, rated by specialists as excellent. Conclusions: the proposed guide contains invariable diagnostic elements and treatment guidelines in order to achieve more comprehensive and efficient malocclusion care.